Between the “southern question” and the “urban question”: The struggle for social justice in touristified southern Italian cities - Pecile, Veronica (Sens public)

(untitled) (Département des littératures de langue française, 2024)
This paper explores the intertwinement of touristification and the commons in contemporary Southern Italian cities. In particular, it sheds light on the articulation of two processes: a “Southern Question”, namely the framing of Southern populations as a “problem” to be overcome through capitalist modernization; and an “Urban Question” as the reshaping of the urban structure under the pressure of the broader economic context and the ruling classes’ strategies. The focus will be on Naples as a city in which both a powerful movement for the urban commons and a profound reconfiguration of the urban economy in a touristic sense are observable in the post-2008 crisis conjuncture. It will be highlighted how the increasing pervasiveness of capitalist capture also opens up new conflictual spaces for renegotiating the city.